Integration of Teacher Exemplary Behavior in Character Education to Build A Globally Perspective Madrasah Generation - Febriyanti Ghayatul Qushwa; Dinda Febrianti Putri; Hasan Jali (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the strategic role of teacher exemplary behavior in character education within madrasahs, with the goal of fostering a generation that upholds both local values and global perspectives. Employing a qualitative case study approach, data were gathered through in-depth interviews with teachers, students, and school administrators, along with observations and document analysis. Thematic and content analysis techniques were applied to derive key themes and patterns from the collected data. The findings indicate that teacher exemplarity significantly influences student character formation through three main factors: strategic interaction with students and parents, the formation of a value-driven school culture, and continuous professional development. Teachers who act as role models and maintain consistent communication with stakeholders contribute to a conducive moral environment. Moreover, the alignment of school vision, leadership, and teacher training plays a pivotal role in sustaining and enhancing character education practices.The implications of this research highlight the necessity of a holistic and collaborative approach to character education involving the entire school ecosystem. It suggests that educational policymakers should strengthen teacher capacity, encourage community involvement, and institutionalize cultural values to ensure the sustainability of character education in madrasahs. These insights are valuable for improving educational strategies aimed at producing ethically grounded and globally aware graduates.